Pengaruh Alat Ekspansi Terhadap Temperatur Dan Tekanan Pada Mesin Pendingin Siklus Kompresi Uap - Hartanto, Boby Hary; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
At this time the more widespread use of engine cooling of homes, offices, hotels, cars, hospitals, and industries. The use of engine cooling capacity varies from small to large. Engine cooling is the most widely used today is the engine cooling operating with vapor compression cycle. One of the basic components that operate the engine cooling vapor compression cycle is the expansion tools. The usefulness of the expansion tools is to reduce the pressure expansion of liquid refrigerant from the condenser exit and regulating the flow of refrigerant into the evaporator entrance. Expansion tools will regulate the flow of refrigerant can be manual or automatic. For optimal cooling requirements, it is important to determine the effect of expansion tools with temperature and pressure of the vapor compression engine cooling cycle is. The test using a thermostatic valve is more efficient compared with the capillary tube, this is due to the use of the thermostatic valve will provide temperature and working pressure lower than the capillary tube, so that the process will lead to greater heat absorption and compressor work will be lighter so the power consumption will be becomes smaller.Keywords :expansion tools, capillary tube, thermostatic expansion valve, refrigerant